Dampak Kebijakan Penghapusan Pajak Progresif dalam Meningkatkan Kepatuhan Wajib Pajak Masyarakat di Kota Padang - Bima Fri Wandra; Adil Mubarak (AHKAM, 2026)
The abolition of progressive tax rates is one of the instruments used by local governments to increase taxpayer compliance while optimizing locally generated revenue (Pendapatan Asli Daerah, PAD). In West Sumatra Province, this policy has been implemented within the framework of a Motor Vehicle Tax incentive program to respond to low taxpayer compliance driven by high tax burdens on owners of more than one vehicle (multiple ownership). This study aimed to analyze the implementation of the policy abolishing progressive tax rates and its impact on taxpayer compliance and PAD realization from the Motor Vehicle Tax sector in Padang City. The analysis was conducted through sequential stages of data reduction, data display, and conclusion drawing to provide a comprehensive picture of policy implementation and its consequences. The findings show that the implementation of the policy abolishing progressive tax rates has been carried out in accordance with prevailing laws and regulations and is supported by user-friendly tax payment services. The policy has had a positive impact on increasing taxpayer compliance and PAD realization from Motor Vehicle Tax in Padang City. However, some impacts are not entirely positive, including an additional burden in the form of a tax surcharge (opsen pajak) and the still suboptimal direct developmental benefits perceived by the community. These findings underscore that the effectiveness of abolishing progressive tax rates is determined not only by regulatory design and administrative services, but also by perceptions of fiscal fairness and a clearly perceived link between tax payments and improvements in the quality of public services.